American Zinc Company’s Operations In The East Tennessee Zinc District - M. J. Langley (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1970)
The American Zinc Company’s mining operations in East Tennessee are located in Knox and Jefferson Counties. Mineralization occurs, intermittently, through a strike length of more than 30 miles, from near the eastern edge of Knoxville northeastward to a few miles beyond Jefferson City. The presence of zinc in these Counties has been known for well over 100 years. In 1910 it was brought to the attention of American Zinc Company that zinc sulphide deposits in the Mascot area might be attractive. Following an examination and some surface prospect drilling, the American Zinc Company of Tennessee was organized and acquired the Mascot properties in 1911. Operations began in 1913 on the basis of 1,000 tons per day mill capacity. With the successful operation of the Mascot mines, the Company undertook explorations in the area from Jefferson City southwest through Friends Station to Mascot. The efforts resulted in development of substantial tonnages of zinc ore and enabled the Company to expand the Mascot and New Market milling operations to their present capacity of 11,100 tons per day. Folded and faulted Paleozoic sedimentary rocks under- lie the mining district. The principal zinc mineralization occurs in a group of strata known as the Knox